2020
DOI: 10.1021/acsomega.9b03751
|View full text |Cite
|
Sign up to set email alerts
|

Ammoxidation of Ethane to Acetonitrile and Ethylene: Reaction Transient Analysis for the Co/HZSM-5 Catalyst

Abstract: Ethane ammoxidation to acetonitrile and ethylene over the Co/HZSM-5 catalysts was revisited based on both transient and steady-state performance evaluation to elucidate the structure/reactivity relationships. We suggested that the exchanged Co 2+ cation encapsulated in the zeolite favors the formation of acetonitrile and ethylene, whereas nanosized cobalt oxide particles without close proximity with the HZSM-5 only favor CO 2 formation. Excess Brønsted acid sites of the zeolites may act as a reservoir for NH 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Since the production of CH 3 CN strongly depends on the acrylonitrile capacity, an on-purpose technique for CH 3 CN production from the cheap and abundant ethane could be an important alternative. Our recent studies have shown that Co- and Sn-modified HZSM-5 catalysts are active for ethane ammoxidation for CH 3 CN. However, as depicted in Figure , the formation of CO 2 and NO x is inevitable under oxidative conditions, which was absent during the anaerobic ADeH.…”
Section: Introductionmentioning
confidence: 96%
“…Since the production of CH 3 CN strongly depends on the acrylonitrile capacity, an on-purpose technique for CH 3 CN production from the cheap and abundant ethane could be an important alternative. Our recent studies have shown that Co- and Sn-modified HZSM-5 catalysts are active for ethane ammoxidation for CH 3 CN. However, as depicted in Figure , the formation of CO 2 and NO x is inevitable under oxidative conditions, which was absent during the anaerobic ADeH.…”
Section: Introductionmentioning
confidence: 96%
“…5 Non-oxidative (EDH) and oxidative (ODH) dehydrogenation of ethane are among the most studied pathways for direct ethane conversion. 6 EDH typically requires high temperatures and low pressures to push the equilibrium toward product formation due to the endothermic nature of the reaction. However, high temperatures can lead to less controllable gas phase reactions between the reactants and products and therefore often lead to equilibrium constraints for EDH reactions.…”
mentioning
confidence: 99%
“…The investigated processes are based upon various routes such as the catalytic reaction between acetylene and ammonia, the reaction between CO, NH 3 , and H 2 over a Mo- or Fe-based catalyst, , and the non-catalytic hydrocyanation of methane with HCN . The preferred and safer processes, however, involve the ammoxidation of ethane or ethylene with the former producing the higher yields to acetonitrile. As shown in Table , independently of the used catalyst, the reached yields are still low (21% as maximum) to be considered for an industrial scale-up. Catalysts for ethane ammoxidation include mixed molybdates, Nb-promoted Ni oxides, Co-exchanged zeolites, MoVNbO mixed oxides containing Te or Sb, and Mo oxides supported on zeolites, with the major byproduct being ethylene.…”
Section: Ethanementioning
confidence: 99%